Dimensi Historis Pendidikan Islam Dinasti Fatimiyyah: (Penyebaran Doktrin Dinasti Fatimiyyah melalui Lembaga Pendidikan) - Maryono Maryono; M. Wahyu Abdi Nugroho (STAI Ali bin Abi Thalib Surabaya, 2021)
The Fatimid dynasty was an dynasty founded by Ubaidillah al-Mahdi with an understanding of Shia Ismailiyah. This dynasty reached its peak of glory when the center of government moved to the Cairo. By that time, Cairo had become the center of Muslim intellectual and scientific activity in the Islamic world. This paper aims to describe the intellectual and scientific development of Islam during the Fatimid dynasty. The method is used in this research is descriptive analysis with a historical approach. This method is a process of critically examining and analyzing past records and relics in the form of written text. The results of the literary analysis carried out show that there was a role for educational institutions during the Fatimid dynasty. Among these educational institutions are; Mosques, Dar al-Ilm and Dar al-Hikmah Libraries, and al-Azhar University. Educational institutions during the Fatimid dynasty were Shia Isma'iliyyah schools with a system of formal, informal, and non-formal educational institutions. In general, educational institutions during the Fatimid dynasty had a big role in the educational revolution in the world. However, it also plays a negative role in Islamic civilization which aims to spread the Shia madzhab in Islamic life.